Perencanaan Kawasan Pariwisata di Kota Tobelo - Stevan Dobiki; Raymond Tarore; Vicky Makarau (Universitas Sam Ratulangi, 2021)
The city of Tobelo has many tourist attractions it's run government and people who live close to the attractions. The city of Tobelo has the potential of a tourist attraction known as luari beach, the island coast of kumo, Kupa-Kupa Beach and Telaga Paca. The tourism support facility has not been adequate, damaged and unavailable and road infrastructure at small tourist spots. Special attention was needed from the city government of tobelo especially the western halmahera tourism service to implement a special strategy planning the existing tourist areas in the city of Tobelo and then the potential for tourism in the city of tobelo could be developed optimally so that no damage to the development of the region itself. The methods used in this study are qualitative and quantitative descriptive by using the SWOT method of analysis. The purpose of this study is to determine the tobelo city's strengths, weaknesses, threats, and opportunities and tourism development strategy correspond to the variable tourism research. The results of this study created internal and external factors for the city of tobelo's tourism development with its development strategy considering existentially conditions consistent with analysis available according analysis results. which is to raise awareness of people, maintain quality of objects, tourist promotion and socialization of the tourist awareness. Keyword : tourism, infrastructure, sosialitation